Tuberculosis in vulnerable populations in Eastern Mediterranean Region—Implications for control. (December 2016) - Shakoor, Sadia; Hasan, Rumina
Abstract: Aims & objectives: Socially and economically disadvantaged or "vulnerable" people are at high risk of tuberculosis (TB) and also contribute to active chains of TB transmission. Included in such vulnerable populations are children, women, prisoners, people living with human immunodeficiency virus, the homeless, and displaced people. The ongoing active transmission of TB among such populations is made more difficult to assess and control by difficult access, health inequities, poverty, and other chronic and debilitating health conditions at individual, domestic, and community levels. Methods: The 22 Eastern Mediterranean Region member states encompass diverse sociopolitical and socioeconomic situations with far-reaching effects on vulnerable populations in each country, thereby threatening the control of TB. Here, we examined the impact of these populations on the incidence and transmission of TB in light of these risks. Results: Approximately 60% of the regional population comprises children and adolescents ⩽19 years of age, increasing the population at risk. Additionally, up to 11% of the population suffers from mental- or substance-abuse disorders, while >50% of the world refugee populations live in the Eastern Mediterranean Region. Conclusion: TB control requires a strategic approach at the country level to access these vulnerable populations.